Estudio del genero Chasicotherium Cabrera y Kraglievich 1931 (Notoungulata - Homaldotheriidae) (Ameghiniana, 2013)
Cabrera and Kraglievich proposed the subfamily Chasicotheriinae (Homalodothelriidae) based on Chasicotherium Cabrera and Kraglievich with the genotype C. rothi, without indication of its characters besides the reduction of teeth. Simpson has not aproved this opinion. The type, an incomplete skull with mandibule, and several other remains of C. rothi C. and K., 1931, from the Chasico are studied. The genus is quite distinctive by the reduced dental formule with I: 2~2/1-1; C: 1-1/1-1; Pm. 4-4/4-4; M. 3-3/3-3. Other characters are: the great bulk, upper canine with the cingule running up and without ridges prototoph very broad in upper molars. Morphologically, Chasicotherium is nearest to Homalodotherium than to Asmodeus or Diorotherium, and is the bigest and more recent Homaldotherid known till present; As Homaldotherium, the premaxillaries are short; the canine is well developped as in the other genera, but without vertical ridges, Pm1 is rudimentary (as in Homalodotheriuln and Diorotherium) and lacks any diastente between upper canine and external incisive. All the characters justifies the maintenance of Chasicotheriinae Cabrera and Kraglievich as a subfamily of Homaldotheriidae.